Conditions of Kejawanan Beach Based on Standard Quality and Suitability for Pollution Index Marine Tourism Area - Nasir Sudirman; Semeidi Husrin; Ruswahyuni Ruswahyuni (Jurnal ILMU DASAR, 2014)
Kejawanan tourist beach is one beach which is located in West Java. This beach is located side to the Kejawanan fishing port. Kejawanan beach topography sloping beach with quiet waters and the waves are not too big. The dominant wind direction throughout the year that influencet the formation of ocean waves are heading toward the bay coast of Cirebon. The existence tourist beach that is located near to the fishing port crowded with activity interesting to known the conditions coast as marine tourism area based on Water quality standars according to Decree of The Minister of Environment Number 51 of 2004. Pollution indeks is based on Decree of The Minister of Environment Number 115 of 2003. Indication of biological contamination by Diversity index of makrobentic animal. The results of the research obtained Water quality standard for marine tourism area mostly exceeded. Pollution index is at the level Heavy pollution. Diversity index of macrobentic animal are at the level of Medium Pollution. Keywords : Kejawanan, standard quality, pollution index, diversity index